Structural insight into a membrane intrinsic Acyltransferase from Chlorobium tepidum - Boral, Debjyoti; Vankudoth, Koteswara Rao; Ramasamy, Sureshkumar (Current Microbiology, 2019)
The Lipid A component of the outer membrane of Gram-negative bacteria is an integral part of the permeability barrier known as LPS, which actively prevents the uptake of bactericidal compounds. It is clinically very significant, as it is known to elicit a strong immune response in the humans, through the TLR4 complex. The Lipid A species are synthesized through a highly conserved multistep biosynthetic pathway. The final step is catalyzed by acyltransferases of the HtrB/MsbB family, which are members of a superfamily of enzymes, present in all domains of life with important roles to play in various biological processes. The investigation of a putative dual functioning enzyme which can add both laurate and myristate residues to the (Kdo)(2)-lipid IVA (precursor of Lipid A) would give a snapshot into the versatility of substrates that these enzymes catalyze. In this study we have cloned and purified to homogeneity, such a putative dual functional acyltransferase from Chlorobium tepidum, and attempted to study the enzyme in more details in terms of its sequence and structural aspects, as it lacks conserved residues with other enzymes of the same family.